Transisi Kepemimpinan Antar Generasi: Studi Kasus di Gereja Kristen Nazarene di Indonesia - Jatmiko, Bakhoh (Sekolah Agama Kristen Terpadu Pesat Salatiga, 2020)
Abstract The multi-generational workplace is a global phenomenon emerges today. In the various organizations worldwide there will be four to five generations working in the same workfore and at the same time. Nazarene Church in Indonesia is now dealing with this phenomenon. Leadership managment related to inter-generational leadership succession strategy has become an insist issue to elaborate. The objectives of this research are to find data of the diversity of the generation in the denomination and to find strategy to tackle the intergerational leadership succession. This research is conducted by collecting the data from the field and also undergoing literature review to examine the previous theories and reseach foundings related to the topic. The research found that the denomination had clergy from four different generations who are ministering together side by side at the same time. The findings also indicate the urgency of a leadership transition inter generations in this church. Therefore, the author proposes some recomendations as the intergenerational leadership transition strategy, namely: mentoring, strengthened intergenerational leadership, intentional leadership development programs, and intergenerational leadership collaboration.Â AbstraksiLingkungan kerja multi generasi adalah fenomena global yang muncul dewasa ini. Di berbagai organisasi di seluruh dunia akan terdapat empat hingga lima generasi yang bekerja ditempat dan waktu yang sama. Gereja Kristen Nazarene di Indonesia pada saat ini sedang menghadapi fenomena tersebut. Pengelolaan kepemimpinan yang berkaitan strategi suksesi kepemimpinan lintas generasi menjadi isu mendesak untuk dikaji. Tujuan dari penelitian ini adalah menemukan data tentang keragaman generasi yang ada di gereja dan untuk menemukan strategi untuk mengatasi persoalan suksesi kepemimpinan antar generasi. Penelitian dilakukan dengan menghimpun data dari lapangan dan juga melakukan studi literatur untuk mengkaji teori-teori dan penelitian terdahulu yang berhubungan dengan topik yang dibahas. Penelitian yang dilakukan menemukan bahwa transisi kempemimpinan lintas generasi merupakan hal mendesak bagi GKN di Indonesia. Oleh karena itu penulis menyampaikan beberapa rekomendasi sebagai strategi transisi kepemimpinan lintas generasi, yaitu: mentoring, penguatan hubungan lintas generasi, program pengembangan kepemimpinan terencana dan kolaborasi kepemimpinan lintas generasi